Shell Scripting Recipes: A Problem-Solution Approach - Johnson, Chris F. A (Apress, 2013)
When I was introduced to Unix in 1990, it was still the domain of multiuser systems and high-end workstations. Even the i386 system I started with had 12 users logging on concurrently through serial terminals. I had remote access through a blazingly fast 1200 bps modem. Things were changing by the mid-1990s, when systems using the Linux kernel, integrated with GNU utilities and the X Window System, provided a viable alternative to Microsoft Windows. At the same time, computers with the power, memory, and hard drive space to run it came within reach of an individual’s pocketbook. The Internet brought fast and efficient distribution of the new systems and software (and enabled their development in the first place). Unix had arrived on the home computer. The twenty-first century has seen the burgeoning of a new breed of Unix user: the home (or small business) user whose computer experience was previously limited, at most, to Microsoft Windows. Such computers may well be used by only one person. This modern user quite likely has no intention of becoming a system administrator, and just wants to use the computer with as little fuss as possible. If that describes you, I hope this book will be an eye-opener. I want to give you a glimpse of the power of the shell. Shell scripts are not just for system administration; they can automate many tasks and solve many different problems. This book is not a tutorial, but by studying the scripts (after reading Chapter 1), you should gain a good grounding in the techniques of shell programming (and most of them can also be used at the command line). If you are an experienced shell scripter, you may find in these pages the scripts you never got around to writing—perhaps even programs you didn’t think could be implemented as shell scripts. A few here had been on my to-do list for years; writing this book gave me the incentive to develop them. I hope you’ll also find interesting techniques and different ways of doing things.